Resultados de la gastrectomía vertical en diabéticos tipo 2 con índice de masa corporal menor a 35 Kg/m 2 - Musleh K., Maher; Lembach J., Hanns (Revista Hospital Clínico Universidad de Chile, 2012)
Vertical gastrectomy (sleeve), has establish edit self as a restrictive bariatric procedure, with the weight loss and resolution of comorbidities comparable to Gastric Bypass. Considered a restrictive procedure, there is still no clarity on the mechanisms of action at entero hormonal that could have an effect on glucose metabolism. There is now consensus in the medical community that weight control in obese diabetic patients, is critical to the management of this disease. It is also the sleeve gastrectomy may have a role in the management of type 2 diabetes in obese patients with BMI under 35 kg/mt2.